MEDIA INFORMASI PENGENALAN MAKNA DAN MOTIF BATIK JAMBI BERBASIS ANDROID PADA SANGGAR BATIK OLAK KEMANG: Information;Batik;Jambi;Meaning. - Surya, Junaidi; Wahyuning Astuti, Reny; Priyanto, Prayit (LP2M Universitas Nurdin Hamzah, 2022)
Batik Jambi was first developed by the families of the Jambi Malay Kings and gradually receded after the kingdom collapsed. The Jambi community, especially many young people, do not know the shape and meaning of the Jambi batik motif, and the difficulty is getting the information about the shape and meaning of the Jambi batik motif because there is no book on the shape and meaning of the Jambi batik motif that can be widely used. If this is allowed to continue it does not rule out the possibility that one day Batik Jambi will be forgotten by the community, especially among today's young generation. The problem is that the Jambi people, especially the younger generation, mostly only know the extent of Batik Jambi, but if asked from the form of the motif even to the meaning of the Jambi batik motif, few know about it because of the lack of information about Batik Jambi which discusses the form and meaning especially in shaped android application.